Primary signet-ring cell carcinoma of the lung: a case report with an immunohistochemical study - Tadashi, Terada (e-Century Publishing Corporation, 2012)
Primary signet-ring cell adenocarcinoma (SRCA) of the lung is very rare. A 78-year-old man consulted to our hospital because of loss of appetite. Physical examination showed lymphadenopathy of the cervical lymph nodes. Chest X-ray showed a tumor of the right upper lobe. Blood laboratory test showed an increase of LDH and CRP. Tumor markers (CYFRA, SCC, CEA, ProGRP) were within normal range. Clinical diagnosis was suspected malignant lymphoma of the lung. Transbronchial lung biopsies showed SRCA (70%) mixed with poorly differentiated adenocarcinoma (30%). The SRCA cells were positive for mucins. Immunohistochemically, the SRCA cells were positive for cytokeratin (CK) AE1/3, CK CAM5.2, CK7, CK18, EMA, p53, Ki-67 (labeling=60%), CEA, CA19-9, TTF-1, and MUC1. They were negative for CK34BE12, CK5/6, CK8, CK14, CK19, CK20, vimentin, chromogranin, synaptophysin, CD45, CD20, CD3, surfactant Apoprotein-A, CDX-2, MUC2, MUC5AC and MUC6. A pathological diagnosis of SRCA of the lung was made. The patient showed downhill course, and died of carcinomatosis 3 months after the first manifestation. In conclusion, a vary rare case of primary pulmonary SRCA was reported with an immunohistochemical study.